Soil N2O emission potential falls along a denitrification phenotype gradient linked to differences in microbiome, rainfall and carbon availability. (November 2020) - Highton, Matthew P.; Bakken, Lars R.; Dörsch, Peter; Wakelin, Steve; de Klein, Cecile A.M.; Molstad, Lars; Morales, Sergio E.
Abstract: Soil denitrification produces the potent greenhouse gas nitrous oxide (N2 O) and by further reduction of N2 O, the harmless inert gas N2 . N2 O emission is determined by rate and timing of the N2 O producing and reducing steps which are sensitive to a series of proximal and distal regulators such as pH and microbial community composition. Microbial community associations to N2 O emission potential (N2 O/(N2 O + N2 )) are commonly entangled with pH leaving the true role of community composition unclear. Here, we leverage a set of soil microbiomes strongly linked to rainfall above pH to test the hypothesis that microbiome vs. N2 O emission potential (N2 O/(N2 O + N2 )) correlations will be maintained across alternative distal drivers. N2 O emission potential (N2 O/(N2 O + N2 )) and denitrification gas (NO, N2 O, N2 ) kinetics were assessed by automated gas chromatography while community composition was assessed by 16 S rRNA gene sequencing and qPCR of nosZI and II genes. Analyses revealed a sustained correlation between microbiome and N2 O emission potential (N2 O/(N2 O + N2 )) in the absence of a pH effect. Further, a continuum of gas accumulation phenotypes linked to NO accumulation and sensitive to carbon addition are identified. Separate phenotypes carried out N2 O production and reduction steps more concurrently or sequentially and thus determined N2 O accumulation and emission potential (N2 O/(N2 O + N2 )). Concurrent N2 O producing/reducing soils typically contained NO accumulation to a low steady state, while carbon addition manipulations which increased NO accumulation also increased sequentiality of N2 O production/reduction and thus emission potential (N2 O/(N2 O + N2 )). These features may indicate a conserved NO inhibitory mechanism across multiple effectors (rainfall, community composition, carbon availability). Highlights: N2 O emission potential is linked to microbiome changes associated with rainfall, but not to pH. Sequential vs. concurrent denitrification phenotypes differing in NO and N2 O accumulation are identified. High N2 O accumulation is associated with increased NO accumulation. Sequentiality of N2 O production/reduction determines soil N2 O emission potential. Sequentiality of N2 O reduction was susceptible to manipulation via carbon addition.